دراسة واقع تطبيق عمليات إدارة المعرفة بكلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير جامعة البليدة 2 من وجهة نظر الهيئة التدريسية: Studying the reality of the application of knowledge management processes at the Faculty of Economics, Commercial Sciences and Management Sciences, University of Blida 2- From the point of view of the faculty - عبدالحق القينعي (Journal of North African Economies, 2025)
The study aimed to know the reality of the application of knowledge management processes into the Faculty of Economics University of Blida 2, Commercial and Management Sciences, according to the teaching staff, the descriptive approach was also used by the study case method, Accordingly, to that, a questionnaire was designed, distributed and analysed by using Spss program, We reached as a result, that the application of knowledge in college under study came at an average level, that’s because the several difficulties and obstacles that prevent the application of knowledge management processes.